KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING PADA PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP PRODUKTIVITAS KERJA PEGAWAI - Dewi Kristiyasari; Indra Prasetyo; Woro Utari (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study is to describe Perceived Organizational Support, Organizational Commitment, and Work Productivity at the Village and Community Empowerment Service of Bojonegoro Regency. To analyze the effect of Perceived Organizational Support and Organizational Commitment on the Work Productivity of employees at the Department of Community and Village Empowerment, Bojonegoro Regency. This research is an explanatory research and uses a quantitative research approach. The population is all employees of the Bojonegoro Regency Community and Village Empowerment Service, totaling 37 people. Total sampling technique or census sampling so that a sample of 37 people is determined. Methods of data collection with questionnaires and documentation. The data analysis technique used in this study uses path analysis which is then processed using Partial Least Square (PLS). The results showed Perceived Organizational Support, Organizational Commitment, and Work Productivity of Employees at the Community and Village Empowerment Service of Bojonegoro Regency in the high category. Perceived Organizational Support and Organizational Commitment all have a significant influence on the Work Productivity of Employees at the Department of Community and Village Empowerment, Bojonegoro Regency